Comprehensive Program for Prevention and Treatment of Dental Caries - Muxiddinov A. L.; Xabibova N. N. (Researchparks Publishing, 2021)
The relevance of the study. Disabilities of children with chronic catarrhal gingivitis, a decrease in the number of gum cells with cytopathological changes, against the background of an increase in the number of cells of the inflammatory infiltrate of PMN and intact monocytes, a decrease in the number of nucleated cells of the spiny layer and non-nuclear keratinized cells, is one of the important links in the pathogenesis of the disease.